SOM BASED ASSURANCE ASSESSMENT FOR INFORMATION SECURITY MANAGEMENT SYSTEM IN ORGANIZATION - Mohammad Akhriza, Tubagus (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2010)
Abstract: Information Security Management System (ISMS) has a lot of standards such as ISO/IEC 27001. In order to assess the quality assurance of ISMS, an organization should design and implement some mechanism. I propose a mechanism for quality assurance assessment using Kohonenâs Self Organizing Map (SOM). SOM is a means for automatically arranging high-dimensional statistical data so that alike inputs are in general mapped close to each other. The resulting map avails itself readily to visualization, and thus the distance relations between different data items can be illustrated in an intuitive manner. This proposal shows that the proposed framework is able to be conducted and implemented. Through this map, the organization will be able to assess how far the organizationâs information security quality has gap with the standard. Not only ISMS ISOâs standard, but also another standard such as Indonesian National Board of Accreditation (BAN-PT).Â Keywords: SOM, Information Security Management System, Quality Assurance